Development of a Teaching Methodology for Undergraduate Human Development in Psychology - Rodríguez, María A. (2015)
The development of a teaching methodology for the undergraduate Psychology course Human Development II in a private university in Lima, Peru is described. The theoretical framework consisted of an integration of Citizen Science and Service Learning, with the application of Information and Communications Technology (ICT), specifically Wikipedia and discussion boards, and fieldwork with Older Adults. Wikipedia, a free digital encyclopedia, allows students to create and edit articles about content within the course. The use of Wikipedia allows students to supplement classroom learning, distinguish between accurate and inaccurate information, and contribute to subject area content online for the public. The teaching methodology aimed to increase critical thinking skills and sense of social responsibility. Fifty-five students of a private university in Lima participated in the course; 26 in the control group during the 2014.1 semester and 29 in the experimental group during the 2014.2 semester. The planning and implementation phases of the methodology, as well as initial qualitative findings are discussed. Analysis of discussions in the student forum indicates that students appeared to utilize more critical thinking skills and demonstrated a sense of social responsibility related to the Older Adult.